2018
DOI: 10.1891/0886-6708.vv-d-17-00174
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Experience of Arab American and Arab Immigrant Women With Intimate Partner Violence

Abstract: This article describes a study resulting from of a university–community partnership. The faculty of the university and the executive director of local community agency serving the local Arab American and Arab immigrant community had a shared interest in looking at the unique experiences and needs of Arab women survivors of intimate partner violence (IPV). This led to a qualitative research project in which 25 Arab American women were interviewed about their experience with IPV. Contextual themes emerged relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…One limitation of this study is that the findings are limited to Arab-American women in an urban setting with a significant Arab-American presence; therefore,the findings may not be generalizable to Arab Americans who are more isolated. However, our findings are similar to past studies with Arab-American women who have survived IPV and live in a large metropolitan area with a large concentration of Arab Americans (Crabtree-Nelson et al, 2018). While there is a necessity for further exploration of the IPV experiences of Arab Americans residing in areas with smaller concentrations of immigrant-origin populations, there are important implications of this study for Arab Americans residing in other cities with significant Arab-Americans populations, including New York, Dearborn, Los Angeles, Chicago, and Washington D.C. (Arab American Institute Foundation, 2018).…”
Section: Limitationssupporting
confidence: 91%
See 3 more Smart Citations
“…One limitation of this study is that the findings are limited to Arab-American women in an urban setting with a significant Arab-American presence; therefore,the findings may not be generalizable to Arab Americans who are more isolated. However, our findings are similar to past studies with Arab-American women who have survived IPV and live in a large metropolitan area with a large concentration of Arab Americans (Crabtree-Nelson et al, 2018). While there is a necessity for further exploration of the IPV experiences of Arab Americans residing in areas with smaller concentrations of immigrant-origin populations, there are important implications of this study for Arab Americans residing in other cities with significant Arab-Americans populations, including New York, Dearborn, Los Angeles, Chicago, and Washington D.C. (Arab American Institute Foundation, 2018).…”
Section: Limitationssupporting
confidence: 91%
“…Stakeholders and clients reported that married Arab-American women who experienced IPV faced challenges due to obstacles created by abusive spouses, family members, and at times, religious leaders. Crabtree-Nelson et al (2018) also found that strong cultural forces play a role in reinforcing a woman's responsibility to follow what her husband says, which has led to women not disclosing abuse to their families. Furthermore, Arab family values play a large role in how Arab-Americans navigate separation and divorce (Barakat, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IPV, which is connected to other forms of violence including exposure to interpersonal‐, societal‐ and state‐level violence (Bacchini et al, 2015; Clark et al, 2010), is of concern in Arab immigrant communities. Arab women face multilevel barriers in reporting IPV and utilization of social services, including shame, family dishonour, self‐blame, traditional social and gender norms, unawareness of resources at the individual and interpersonal levels and increased stereotypes, racism and Islamophobia in the community and societal levels (Crabtree‐Nelson et al, 2018; Kulwicki et al, 2015). There are no published studies focused on IPV prevention amongst Arab Americans.…”
Section: Introductionmentioning
confidence: 99%